Prelaunch radiometric calibration of the HIRDLS flight instrument: Results and use in on-orbit data processing - Eden, T; Gille, J; Barnett, J; Hepplewhite, C; Whitney, J; Arter, P; Peters, D; Watkins, R (Institute of Electrical and Electronics Engineers Inc., 2014)
Results from the prelaunch radiometric calibration of the 21-channel High Resolution Dynamics Limb Sounder (HIRDLS) flight instrument are presented. The calibration was carried out in the Department of Physics of Oxford University. Two large aperture external blackbody cavities were used to generate stable radiances at target temperatures between ~90 and ~320 K. These blackbodies were located, along with the HIRDLS instrument, inside a large vacuum chamber. Data were taken at three different focal-plane temperatures ( ~61, ~66, and ~71 K). To complicate matters beyond the initial scope of the prelaunch calibration, a failure of some contamination close-out material (Kapton) that lined the inner fore-optics cavity occurred during launch, which made the original in-flight radiometric calibration procedure impossible. Accordingly, the radiometric conversion algorithm had to be changed, requiring more information from prelaunch calibration to be used than first envisioned. This paper discusses a variety of details, such as data-taking procedures, analysis methodology, associated error analyses, and necessary changes to the radiometric conversion algorithm needed for in-flight data processing. © 1980-2012 IEEE.